Managing the electronic government : from vision to practice - Schedler, Kuno; Summermatter, Lukas; Schmidt, Bernhard (Research in public management., 2004)
This book provides an insight into the possibilities that so-called "Electronic Government" has to offer. It demonstrates the elements belonging to the concept of E-Government and acts as a point of reference for those aiming to implement it. Checklists and lists of questions enable self-assessment at local, state and federal levels, highlighting opportunities for further development. The book cannot be described as technical--programmers will not find any instructions. Instead, it is designed to act as a point of orientation for decision makers in the field of government and politics, without the need to get bogged down in technical details. Central to the book are the following questions: what is Electronic Government, what advantages does it bring to those involved with it, and how can it be introduced?